Medicinal Plant Biotechnology - Arora, Rajesh (CABI, 2014)
The ancient physicians of India said and proved that ‘there is no plant in this world which is not a medicine’. Scientists too have begun to realize that if we intend to provide affordable and accessible healthcare globally, we should sustainably utilize the available medicinal plant biodiversity. Plant-derived drugs can be a panacea, provided we utilize them on a scientific basis. Medicinal and aromatic plants (MAPs) are nature’s gift and have been used for allaying disease and improving the quality of life for ages. The area of medicinal plants is once again witnessing burgeoning interest in view of their colossal potential to prevent and cure virtually any disease. MAPs continue to and will remain invaluable sources of new chemical entities in future. In recent years compounds derived from MAPs have been commercially exploited by the pharma, food, flavour, fragrance, dyeing and pesticide industry. The disparate relationship between demand and supply has necessitated conventional and modern research in the field. A paradigm shift towards biotechnological applications is evident since modern biotech tools offer novel opportunities not only for improved production of useful compounds, but also development of designer plants, a feat impossible to accomplish by conventional approaches. The future appears bright, but the proof of the pudding lies in the fact that the designer crops should find commercial application and a long way would have to be traversed before the lab to land to market concept becomes a reality. The present book has been conceived with the intention of providing the state-of-the- art in the subject and discusses the various facets in the light of contemporary developments. The book is organized into ten major sections. Section I highlights the emerging trends in medicinal plant biotechnology, emphasizing the current state of expertise available at the hands of researchers for production of a plethora of medicinal compounds in plants cell factories. Indiscriminate population growth, coupled with urbanization and overharvesting has led to erosion of precious genetic resources. In addition, extensive human intervention has resulted in global climate change, which is taking a heavy toll on natural biodiversity. Further climate change might usher in more vagaries of environment and several medicinal plant species may become endangered or extinct in coming times. The need of the hour is to conserve the MAPs and step up efforts to develop improved diverse environment- tolerant strains. Section II discusses the tools available for conservation of genetic resources, and the potential and opportunities of microsatellite markers in genetic diversity screening.